Evolution of self‐incompatibility in the Brassicaceae: Lessons from a textbook example of natural selection. (3rd March 2020) - Durand, Eléonore; Chantreau, Maxime; Le Veve, Audrey; Stetsenko, Roman; Dubin, Manu; Genete, Mathieu; Llaurens, Violaine; Poux, Céline; Roux, Camille; Billiard, Sylvain; Vekemans, Xavier; Castric, Vincent
Abstract: Self‐incompatibility (SI) is a self‐recognition genetic system enforcing outcrossing in hermaphroditic flowering plants and results in one of the arguably best understood forms of natural (balancing) selection maintaining genetic variation over long evolutionary times. A rich theoretical and empirical population genetics literature has considerably clarified how the distribution of SI phenotypes translates into fitness differences among individuals by a combination of inbreeding avoidance and rare‐allele advantage. At the same time, the molecular mechanisms by which self‐pollen is specifically recognized and rejected have been described in exquisite details in several model organisms, such that the genotype‐to‐phenotype map is also pretty well understood, notably in the Brassicaceae. Here, we review recent advances in these two fronts and illustrate how the joint availability of detailed characterization of genotype‐to‐phenotype and phenotype‐to‐fitness maps on a single genetic system (plant self‐incompatibility) provides the opportunity to understand the evolutionary process in a unique perspective, bringing novel insight on general questions about the emergence, maintenance, and diversification of a complex genetic system.